(untitled) (Scientific journal of the Fergana State University, 2024)
In light of the current trend towards miniaturization of electronic devices and instruments, considerable attention is paid to the study of the properties of thin polycrystalline films of semiconductors, which play a key role in modern electronics. Of particular interest are the interfaces in such structures, which can influence their properties and create new opportunities for the development of devices with unique characteristics. This paper presents methods for studying the role of the effective density of electronic surface states in heterogeneous Bi2Te3-Sb2Te3 films. This research approach aims to gain a deeper understanding of the physical processes occurring in such systems and can contribute to the development of new materials and technologies in the field of nanoelectronics.